The Role of Multidimensional Prognostic Index to Identify Hospitalized Older Adults with COVID-19 Who Can Benefit from Remdesivir Treatment: An Observational, Prospective, Multicenter Study - Custodero, Carlo; Veronese, Nicola; Topinkova, Eva; Michalkova, Helena; Polidori, Maria Cristina; Cella, Alberto; Cruz-Jentoft, Alfonso J; von Arnim, Christine A F; Azzini, Margherita; Gruner, Heidi; Castagna, Alberto; Cenderello, Giovanni; et al. (Drugs & aging, 2023)
BACKGROUND: Data regarding the importance of multidimensional frailty to guide clinical decision making for remdesivir use in older patients with coronavirus disease 2019 (COVID-19) are largely unexplored. OBJECTIVE: The aim of this research was to evaluate if the Multidimensional Prognostic Index (MPI), a multidimensional frailty tool based on the Comprehensive Geriatric Assessment (CGA), may help physicians in identifying older hospitalized patients affected by COVID-19 who might benefit from the use of remdesivir. METHODS: This was a multicenter, prospective study of older adults hospitalized for COVID-19 in 10 European hospitals, followed-up for 90 days after hospital discharge. A standardized CGA was performed at hospital admission and the MPI was calculated, with a final score ranging between 0 (lowest mortality risk) and 1 (highest mortality risk). We assessed survival with Cox regression, and the impact of remdesivir on mortality (overall and in hospital) with propensity score analysis, stratified by MPI = 0.50. RESULTS: Among 496 older adults hospitalized for COVID-19 (mean age 80 years, female 59.9%), 140 (28.2% of patients) were treated with remdesivir. During the 90 days of follow-up, 175 deaths were reported, 115 in hospital. Remdesivir treatment significantly reduced the risk of overall mortality (hazard ratio [HR] 0.54, 95% confidence interval CI 0.35-0.83 in the propensity score analysis) in the sample as whole. Stratifying the population, based on MPI score, the effect was observed only in less frail participants (HR 0.47, 95% CI 0.22-0.96 in propensity score analysis), but not in frailer subjects. In-hospital mortality was not influenced by remdesivir use. CONCLUSIONS: MPI could help to identify less frail older adults hospitalized for COVID-19 who could benefit more from remdesivir treatment in terms of long-term survival.
Keywords: prognóza; COVID-19 Drug Treatment; Aged; Prospective Studies; senioři; farmakoterapie COVID-19; geriatrické hodnocení; senioři nad 80 let; lidé; ženské pohlaví; Frailty; Humans; Aged, 80 and over; křehkost; Prognosis; Female; Geriatric Assessment; COVID-19; prospektivní studie